Learner preferences regarding integrating, sequencing and aligning virtual patients with other activities in the undergraduate medical curriculum: A focus group study - Huwendiek, Sören; Duncker, Cecilia; Reichert, Friedrich; De Leng, Bas A.; Dolmans, Diana; van der Vleuten, Cees P. M.; Haag, Martin; Hoffmann, Georg F.; Tönshoff, Burkhard (Medical teacher, 2013)
Context: E-learning resources, such as virtual patients (VPs), can be more effective when they are integrated in the curriculum. To gain insights that can inform guidelines for the curricular integration of VPs, we explored students’ perceptions of scenarios with integrated and non-integrated VPs aimed at promoting clinical reasoning skills.Methods: During their paediatric clerkship, 116 fifth-year medical students were given at least ten VPs embedded in eight integrated scenarios and as non-integrated add-ons. The scenarios differed in the sequencing and alignment of VPs and related educational activities, tutor involvement, number of VPs, relevance to assessment and involvement of real patients. We sought students’ perceptions on the VP scenarios in focus group interviews with eight groups of 4-7 randomly selected students (n = 39). The interviews were recorded, transcribed and analysed qualitatively.Results: The analysis resulted in six themes reflecting students’ perceptions of important features for effective curricular integration of VPs: (i) continuous and stable online access, (ii) increasing complexity, adapted to students’ knowledge, (iii) VP-related workload offset by elimination of other activities, (iv) optimal sequencing (e.g.: lecture - 1 to 2 VP(s) - tutor-led small group discussion - real patient) and (V) optimal alignment of VPs and educational activities, (vi) inclusion of VP topics in assessment.Conclusions: The themes appear to offer starting points for the development of a framework to guide the curricular integration of VPs. Their impact needs to be confirmed by studies using quantitative controlled designs.
Gesehen am 22.12.2021